Sexuality now - Janell L. Carroll (Wadsworth/Thomson Learning, 2007)
This study guide is written by Shirley Ogletree of Texas State University, San Marcos, and contains the following for every chapter: chapter summary, learning objectives, detailed chapter outline, personal assessments & activities, one paper assignment per chapter, 15 fill-in-the blank questions per main sub-head, five short answer per main sub-head, labeling of anatomy art in appropriate chapters, and a post-test consisting of 10 true/false, 30 multiple-choice, and 10 matching quiz questions covering the entire chapter. The answers, rejoinders and main text page references for all quiz items will be included at the end of each chapter